Power Generation and Voltage Regulation of 132KV Karbala Grid using DFIG Wind Turbine Generator - Qasim Kamil Mohsin; Xiangning Lin; Owolabi Sunday; Asad Waqar (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Due to increasing demand on electrical energy in Iraq and to have clean energy that is environmental friendly, wind energy would be one of the most important and promising sources of renewable energy to achieve this goal. This paper discussed the reasons to use the Doubly-Feed Induction Generator (DFIG) amongst the available types of wind turbine generators, and in section (4) illustrate Motivations to select place to the wind farm construction. using decupling method (the vector control strategy) to change reactive power of DFIG 2MW connected to middle of the 132KV transmission line (Karbala north – Alahkader) without effect about the active power generated from DFIG itself with fixed wind speed value assumed to provide the voltage regulation, and control of the transmission line In addition to power generating. By using PSCAD/EMTDC, different simulation results are presented based on various scenarios.